Incidence of mycosis fungoides in patients with chronic psoriasis vulgaris - Navarro Lambraño, Mayra Alejandra; Vallejo, Valeria (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Background: Psoriasis is a chronic dermatosis, characterized by erythematous and scaly plaques, affecting 2 -3% of people worldwide. And on the other hand we have mycosis fungoides, the most common cutaneous T-cell lymphoma, which presents manifestations that vary from erythematous macules to tumors. These two pathologies are independent, however, their clinical and pathological similarity has generated erroneous diagnoses. However, literature has marked a possible connection between the two. The relationship between psoriasis and mycosis fungoides, as well as the appearance of mycosis fungoides after systemic treatment for psoriasis, has generated a great enigma and really requires exhaustive study. Material and methods: A systematic review of publications of studies on the incidence of mycosis fungoides in chronic psoriasis vulgaris patients is carried out, and a meta-analysis will be carried out that incorporates all the published information available using the online databases pubmed, google scholar, trip medical database, Embase, prospero International prospective register of systematic reviews Results: The systematic review concluded that 47 cases met the inclusion criteria, that is, patients with a history of long-standing psoriasis vulgaris, of which 38 patients received biological therapy and 32 patients developed mycosis fungoides. Conclusion: The association between mycosis fungoides and long-standing psoriasis vulgaris is a complex issue, mainly due to its difficulty in clinically differentiating both diseases, which often generates an erroneous diagnosis. Likewise, there have been cases of coexistence of both pathologies and the appearance of mycosis fungoides secondary to long-standing treatments for psoriasis vulgaris. A clear association between psoriasis and mycosis fungoides has not yet been established. However, it is possible that this connection is favored by the immunopathology of psoriasis due to the constant activation of the immune system and the presence of Th17 cells, predisposing to the development of mycosis fungoides. However, there are few studies on these topics specifically. It is imperative that more studies be conducted to understand the mechanisms involved, develop and establish more specific management guidelines against therapies for patients with pre-existing risk factors. Some studies have suggested an association between the use of biologic therapies for psoriasis and an increased risk of developing or exacerbating mycosis fungoides in certain patients. However, the evidence is still inconclusive and more research is needed to fully understand this relationship. Concern about the impact of immunological therapies in long-standing psoriasis vulgaris highlights the need for constant monitoring and long-term investigations to better understand the long-term effects of these treatments. The actual incidence and prevalence of the relationship between long-standing psoriasis vulgaris and mycosis fungoides cannot be determined with certainty